Financing technology transfer: assessment of university-oriented proof-of-concept programmes. Issue 2 (7th February 2017) - Munari, Federico; Sobrero, Maurizio; Toschi, Laura
ABSTRACT: This study analyses the characteristics of the proof-of-concept (POC) programmes initiated by university and public research organisations in Europe, as a mechanism to address funding gaps and improve the transfer of research-based inventions to markets. We contribute to the literature on investment readiness of new ventures and on financing technology transfer by assessing the structure of such funding instruments and identifying critical success factors for their design and implementation. The analyses rely on seven in-depth case studies of university-oriented POCs in Europe.